WIRELESS OPTICAL COMMUNICATION TECHNOLOGIES IN 5G AND 6G NETWORK INFRASTRUCTURE: PROBLEMS AND SOLUTIONS - Javid J. Aghashov; Tabriz J. Aghashov (Problems of Information Society)
The article broadly examines the importance of choosing a wireless data transmission technology in 5G and 6G networks with speeds exceeding 1 Gbit/s, the methods and advantages of technological solutions applied in this area, and also conducts a comparative analysis of various approaches in order to increase efficiency in accordance with the increasing data transmission requirements of the modern era. Scientific research conducted in this area reveals serious problems related to the existing technological shortcomings of the data transmission method using radio waves, in particular, the limited ability to meet the requirements for high-volume data transmission, as well as the impossibility of effective use of radio communication channels in 5G and 6G networks due to technological and physical limitations. These problems are mainly related to the lack of sufficient spectrum resources, increased electromagnetic interference, and signal attenuation over space and time. Consequently, the continuous development of communication technologies and the search for alternative methods remain a priority for solving urgent problems in this field. In this regard, the article describes the features, main characteristics and requirements of new generation mobile networks (5G/6G). The classification of wireless optical communication technologies, their physical characteristics, working principle and comparative analysis with other wireless technologies are reviewed. The issues raised in this work are explored and summarized. According to the results of the study, the successful installation of optical communication 5G/6G networks can be used as an effective solution.